Sensitivity and Specificity of Electrocardiographic Criteria for Left Ventricular Hypertrophy in Children with Rheumatic Heart Disease - Sudigdo Sastroasmoro; Bambang Madiyono; Ismet N. Oesman (Paediatrica Indonesiana, 1991)
Electrocardiographic criteria for left ventricular hypertrophy (L VH) were examined in 84 unselected pediatric patients with rheumatic heart disease. There were 47 male and 3 7 female patients, ranging in age from 6 to 19 years. Electrocardiographic L VH was detected m 41 patients (48.8%), i.e. in 55.3% (26/47) of boys and in 36.6% (15/41) of girls. Echocardiographically determined L VH was present in 42 cases (50%) if left ventricular mass (L VM) was indexed for height, or 47 cases (56%) if L VM was indexed for body surface area (BSA). The overall sensitivity of height-indexed electrocardiographic diagnosis of LVH was 71.4% (95% confidence interval= 57.7% to 85.1%), while its sensitivity was 73.8% (95% confidence interval= 60.0% to 87.0%). For BSA indexed echocardiographic LVH, the sensitivity was 68.1% (95% confidence interval = 54.8 to 81.4%) and the specificity was 75.7% (95% confidence interval = 61.9% to 89.5%). When sex-adjustment was examined, there was no increase of sensitivity of electrocardiographic LVH. Sensitivity of the electrocardiogram for LVH increased when age-adjustment was examined with 13 years of age as a cut-off point, both for height indexed and BSA-indexed echocardiographic LVH. Reasons/or the difference between these findings and the findings in adult patients (remarkably low sensitivity and very high specificity of ECG L VH) were discussed. Electrocardiogram was a moderate diagnostic modality in the detection of L VH in our pediatric patients with rheumatic heart disease. Sex did not influence the sensitivity of ECG L VH, but older age group tended to increase its sensitivity.